On the availability of the name Poecilia kempkesi Poeser 2013 (Cyprinodontiformes: Poeciliidae) - Bragança, Pedro H. N.; Ottoni, Felipe P. (Zootaxa, 2021)
The poeciliid species, Poecilia kempkesi Poeser, 2013, was the fourth species of the subgenus Acanthophacelus Eigenmann, 1907 to be described, based on individuals from a single urban anthropized locality close to Paramaribo, Suriname (Poeser, 2013). The description itself lacked any section clearly distinguishing the new species from the remaining species of Poecilia Bloch & Schneider 1801, and in particular from the species of the subgenus Acanthophacelus, type species Poecilia reticulata Peters, 1859. According to Article 13 of the International Code of Zoological Nomenclature (ICZN, 1999) the criteria of availability for a species-group name are: